Achieving simultaneous biological COD and phosphorus removal in a continuous anaerobic/aerobic A-stage system. (15th February 2021) - Zhang, Congcong; Guisasola, Albert; Baeza, Juan Antonio
Highlights: Enhanced Biological Phosphorus Removal (EBPR) at short sludge retention time (SRT) A-Stage EBPR is achieved as a high-rate anaerobic/aerobic system at low SRT = 4d No nitrification is observed operating at aerobic DO = 0.5 mg/L and SRT = 4d 64% of entering COD is diverted to biomass for energy recovery 69% of N in the influent remains as NH4 + in the effluent for the B-stage treatment Abstract: Recovering energy from wastewater in addition to its treatment is a hot trend in the new concept of water resource recovery facility (WRRF). High-rate systems operating at low solid retention time (SRT) have been proposed to meet this challenge. In this paper, the integration of Enhanced Biological Phosphorus Removal (EBPR) in an anaerobic/aerobic continuous high-rate system (A-stage EBPR) was evaluated. Successful P and COD removal were obtained operating at SRT 6, 5 and 4 days treating real wastewater, while a further decrease to 3 days led to biomass washout. The best steady state operational conditions were obtained at SRT = 4d, with high removal percentage of P (94.5%) and COD (96.3%), and without detecting nitrification. COD mineralization could be reduced to 30%, while 64 % of the entering carbon could be diverted as biomass to energy recovery. Regarding nitrogen, about 69±1% of the influent N was left as ammonium in the effluent, with 30% used for biomass growth. The aerobic reactor could be operated at low dissolved oxygen (DO) (0.5 mg/L), which is beneficial to decrease energy requirements. Biochemical methane potential (BMP) tests showed better productivity for the anaerobic sludge than the aerobic sludge, with an optimal BMP of 296±2 mL CH4 /gVSS. FISH analysis at SRT = 4d revealed a high abundance of Accumulibacter (33±13%) and lower proportion of GAO: Competibacter (3.0±0.3%), Defluviicoccus I (0.6±0.1%) and Defluviicoccus II (4.3±1.1%). Graphical abstract: Image, graphical abstract